The Official Endowment between Ethical Incentive and Paradigmatic Employment: A Study of Israeli Jewish Writings on the Crusader Era - Amezzian, Mohammed (Islamic Studies, 2024)
The growth of endowment institutions and charitable activities witnessed significant expansion during political transitions in the Levant, Iraq, and Egypt. Notably, this trend became more pronounced following the post-Crusades with the Zengid, Ayyubid, and Mamlūk states. These institutions and charitable endeavours became a focal point for many Jewish scholars and Israelis who devoted considerable scholarly attention to understanding the religious, social, and political dimensions of this phenomenon. This paper posits the fundamental hypothesis that these scholarly inquiries were influenced by religious and political considerations, thereby shaping Jewish memory. This memory, in turn, contributes to a reinterpretation of the region’s history, leaning more towards a politically biased agenda than an objective pursuit of knowledge. Within this context, the paper seeks to unravel the paradigmatic approach that scrutinizes the ethical motivations behind charitable works, alleging that those in charge manipulated them for propaganda and political objectives to secure personal gains. To examine this hypothesis, the paper delves into the ideological foundations underpinning this skewed interpretation. It critically evaluates a selection of research conducted by a cohort of historians within a broad spectrum of Jewish scholars who share a similar methodological approach and arrive at analogous conclusions.